Health education using the video based learning (VBL) method on the knowledge level of scabies prevention in adolescents - Azizah, Alicia Syafa; Rizqiea, Noerma Shovie; Utami, Ratih Dwilestari Puji (Media Keperawatan Indonesia, 2024)
Scabies is a contagious skin disease characterized by itching at night. Scabies prevention started from the knowledge level of scabies prevention. Health education using the Video Based Learning (VBL) method is an effort to increase scabies prevention knowledge. The study aimed to determine the effect of health education using the Video Based Learning (VBL) method on the knowledge level of scabies prevention in adolescents at the Al Ibanah Islamic Boarding School of Wonogiri. The research adopted a quantitative using a quasi-experiment method with pre and post-tests without a control group. The research population was 188 respondents with a total sampling technique. The research instrument used a questionnaire on the knowledge level of scabies prevention and tested for validity and reliability. The results presented that the average age of the respondents was 14.15 years, and they were female. The knowledge level in pre-health education using the Video Based Learning (VBL) method was good for 102 (54.3%) respondents. Post-health education with the Video Based Learning (VBL) method was good for 171 (91%) respondents. The results of the Wilcoxon test show a P-value of 0.000 (P-value <0.05). There was an effect of health education using the Video Based Learning (VBL) method on the knowledge level of scabies prevention.